INTEGRATING CASHEW (ANACARDIUM OCCIDENTALE) WITH FOOD CROPS: PERCEPTIONS OF FARMERS AT AMOMA, IN THE KINTAMPO SOUTH DISTRICT OF THE BONO EAST REGION OF GHANA - Louisa Adomaa OFORI; Eunice NIMO; John Tennyson AFELE; Olivia AGBENYEGA (Journal of Applied Life Sciences and Environment)
Income maximization from cashew products and proper utilization of resources has significantly evolved in Amoma, as a result of cashew diversification with food crops. The aim of the study was to assess the perceptions of farmers on integrating cashew with food crops. The study aimed to identify the type of food crops intercropped with cashew, as well as reasons and its associated challenges. A total of 83 respondents were purposively sampled from four communities (Asesase, Kukuroase, Tutuoase and Afapemu). The results indicated that all farmers had knowledge on food crops integration with cashew. Amongst the food crops cultivated with cashew include yam, maize, cassava and groundnut. Reasons stated for integration of food crops include weed control, subsistence use and also financial safety nets. Farmers’ major challenge was financial and also weeds control on their farm. The study concluded that yam was the commonest intercrop of cashew followed maize. Key challenges encountered by farmers were weed invasion and inadequate disposable cash for maintenance practices, such pruning and weeding. In pursuit of achieving the Sustainable Development Goals 1 (No Poverty) and 2 (Zero Hunger), the study recommends that farmers be trained on proper food crop integration methods at Amoma to boost yield, financial stability and enhance living conditions.